Um Cartulário Bracarense do Século XIV: o “Livro das Cadeias” - Cunha, Maria Cristina Almeida e (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The Liber Fidei is undoubtedly the best known medieval cartulary in the Cathedral of Braga, particularly because of its juridical, diplomatic and historical importance. The whole document was fully published by Professor Avelino de Jesus da Costa. However, other Cartularies deposited in the Braga District Archive are not as well-known. This is the case of the “Livro das Cadeias”, a cartulary comprising 112 copies of documents dating from 1112 to 1345, some of which have already been published in various scientifi c papers. Yet, the whole collection of documents that constitutes this cartulary still lacks a comprehensive study, namely about the reasons that lead to its organization. This is the objective of our study.